2015
DOI: 10.1176/appi.ajp.2014.14050578
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Small Vessel Disease and Association With Higher Incidence of Depressive Symptoms in a General Elderly Population: The AGES-Reykjavik Study

Abstract: Objective The vascular depression hypothesis postulates that cerebral small vessel disease (CSVD) leads to depressive symptoms via disruption of brain structures involved in mood regulation. However, longitudinal data on the association between CSVD and depressive symptoms are scarce. We investigated the association between CSVD and incident depressive symptoms. Methods Longitudinal data are from the AGES-Reykjavik study of 1,949 participants free of dementia and without baseline depressive symptoms (74.6 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
123
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 119 publications
(131 citation statements)
references
References 40 publications
4
123
2
2
Order By: Relevance
“…Previous studies reported a mean white matter lesion volume of 5 to 11 mL in participants with a mean age of 72 to 75 years. [25][26][27] The prevalence of cerebral microbleeds and lacunar infarcts in our study population (25.0% and 27.6%, respectively) was slightly higher than that in other studies, reporting a prevalence of cerebral microbleeds of 17.2% 27 or 23.5% and a prevalence of lacunar infarcts of 18.2%. 26,28 Although cerebrovascular reactivity may be reduced in persons with small vessel disease, 23,24 BP was not related to CBF in subgroups of persons with overt signs of small vessel diseaserelated pathologies.…”
Section: Discussioncontrasting
confidence: 78%
“…Previous studies reported a mean white matter lesion volume of 5 to 11 mL in participants with a mean age of 72 to 75 years. [25][26][27] The prevalence of cerebral microbleeds and lacunar infarcts in our study population (25.0% and 27.6%, respectively) was slightly higher than that in other studies, reporting a prevalence of cerebral microbleeds of 17.2% 27 or 23.5% and a prevalence of lacunar infarcts of 18.2%. 26,28 Although cerebrovascular reactivity may be reduced in persons with small vessel disease, 23,24 BP was not related to CBF in subgroups of persons with overt signs of small vessel diseaserelated pathologies.…”
Section: Discussioncontrasting
confidence: 78%
“…Microbleeds were associated with LLD but not with EOD [146]; these lesions and WMHs were associated with cerebral small vessel disease (CSVD) and reduced cerebral blood flow [148], which predicted depressive disorder in healthy older adults [149]. Depressive symptoms were seen in 10.1–39.8 % of patients with CSVD [2, 150], and patients with silent cerebral infarcts and chronic heart failure had an increased prevalence of MDD compared to those without chronic heart failure [151]; further, minor cerebrovascular incidents predisposed patients to LLD/VaDep [152]. Lacunar infarcts in deep white matter were associated with greater psychomotor retardation, motivation and energy loss, depressed mood, and cognitive decline, presumably due to disruption of frontal–subcortical networks [153, 154], while others suggested that apathy, but not depression in CSVD, is related to damage in circuits associated with emotion regulation [155].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, in particular in the pallidum and putamen, dilated Virchow-Robin spaces may be a marker for vascular damage directly caused by high pressure variability and flow pulsatility, as was demonstrated in the AGES-Reykjavik Study. 74 Although the mechanisms by which dilated Virchow–Robin spaces are formed are not completely elucidated, they particularly occur in the pallidum and putamen, in its worst form known as “état criblé” describing diffusely widened perivascular spaces. Widened perivascular spaces are also a common finding in deep white matter in older and/or hypertensive persons.…”
Section: Mri Of Brain Small Vessel Disease and Aortic Functionmentioning
confidence: 99%